(untitled) (Bangladesh Journal of Psychiatry, 2017)
Obsessive-Compulsive Disorder (OCD) is a severe and debilitating anxiety disorder which causes severely impaired quality of life. The objective of the study was to assess the quality of life of the patients suffering from OCD. It was a cross-sectional study conducted from January 2011 to June 2011 among 46 patients who attended the out-patient department of the National Institute of Mental Health Sher-E-Bangla Nagar, Dhaka, Bangladesh and Holy Family Red Crescent Medical College and Hospital, Dhaka, Bangladesh by using purposive sampling technique. A Semi-structured questionnaire, Dhaka University Obsessive Compulsive Scale (DUOCS), World Health Organization Quality of Life-Scale Brief Version (WHOQOL-BREF), Diagnostic and Statistical Manual for Mental Disorder, 4th edition (DSM-IV) were used in each case for this assessment. Results showed that mean age of the patients was (29.07±6.11) years, majority of the respondents (71.7%) were male, 63.0% were unmarried and 34.8% were students. Patients were least satisfied with social domain and patients having only obsession had lower mean score (23.54±1.80) in environmental domain than in patients having both obsession and compulsion (25.15±3.70). OCD patients having major conflict (52.2%) were least satisfied with environmental health domain and patients suffering from OCD for more than ten years (78.3%) had low score than those suffering for less than ten years (21.7%) in overall quality of life domain. Patients having strained family relationship (34.8%) were less satisfied to psychological health domain and patients getting medication (91.3%) had better quality of life in all domains than those getting no medication (8.7%). Bang J Psychiatry June 2015; 29(1): 18-22